4D‐Printed Biodegradable and Remotely Controllable Shape Memory Occlusion Devices. (8th October 2019) - Lin, Cheng; Lv, Jinxin; Li, Yuanshi; Zhang, Fenghua; Li, Jinrong; Liu, Yanju; Liu, Liwu; Leng, Jinsong
Abstract: Implantation of occlusion devices is an effective approach for the treatment of congenital heart diseases in the clinic. However, most commercial clinical occlusion devices are currently made of nondegradable metals, which may lead to complications such as perforation, allergies, and erosion. In this work, 4D‐printed novel, biodegradable, remotely controllable, and personalized shape memory occlusion devices are demonstrated and atrial septal defect occluders are exemplified. By incorporating Fe3 O4 magnetic particles into the shape memory poly(lactic acid) matrix, the deployment of the occluders can be controlled remotely after implantation. The excellent cytocompatibility and histocompatibility are conducive to cell adhesion and ingrowth of granulation tissues into the occluders, thus facilitating rapid endothelialization. In addition, personalized shape memory occluders ensure an ideal fit and provide sufficient support for defects. Therefore, 4D‐printed shape memory occluders can be used as a potential substitute for metal occlusion devices. Abstract : 4D printed novel, biodegradable, remotely controllable, and personalized shape memory occluders are proposed. The occluders can avoid serious complications that are caused by using metal occluders and can avoid potential dangers of nondegradable metal occluders remaining in the body forever. In addition, their good biocompatibility facilitates endothelialization, and excellent shape recovery performance ensures a rapid and perfect sealing of defects.